Quality of raw milk from small producers of the Cayambe and Pedro Moncayo cantons, Ecuador, through physicochemical analysis and qualitative tests - Salguero, Armando (2023)
The northern area of Pichincha-Ecuador is the second most important dairy region in the province after the Mejía canton, so the aim of this study was to determine, based on the Ecuadorian Technical Standard INEN 9, the quality of raw milk marketed by small and medium producers from the Cayambe and Pedro Moncayo cantons. Samples were collected from 22 points of collection centres and cattle farms, with intervals of 15 days between collections (total: 132 samples). The samples were collected from the cold storage tanks between February and April 2019 (rainy season). The qualitative tests and physicochemical analyses were carried out in the Milk Quality Laboratory of the Uyumbicho Experimental Centre of the Central University of Ecuador. The results showed that only 6.82% (9/132) fail to comply with one or several parameters. All the samples were within the norms for density, fat, total solids, chloride concentration, absence of starches, hydrogen peroxide, colorants and antibiotics. Besides, 98.5% (130/132), 99.2% (131/132), 95.5% (126/132) and 99.2% (131/132) complied with the protein stability, neutralizers, titratable acidity and pH, respectively. In conclusion, most of the milk samples analysed comply with Ecuadorian legislation, showing that there are still quality assurance procedures that must be improved by producers and collection centres.